Facilitating Cross-Border Mobile Banking in Southern Africa - Maimbo, Samuel; Saranga, Tania; Strychacz, Nicholas (World Bank, Washington, DC, 2012)
The use of mobile banking is an increasingly important component of national and regional economic development in Southern Africa. Mobile banking can help bring the large unbanked population into the formal financial sector, and can facilitate cross-border trade by easing the difficulty for small businesses and traders to make financial transactions. For mobile banking to reach its full potential in Southern Africa, however, African governments must establish more efficient regulatory frameworks and implement well-designed pilot programs to gain more insight into the challenges facing a full rollout of mobile banking.